Dynamics of aqueous binary glass-formers confined in MCM-41. Issue 19 (21st May 2015) - Elamin, Khalid; Jansson, Helén; Swenson, Jan
<x xml:space="preserve">Abstract</x> A typical fit of dielectric loss data (left) and glass transition temperatures of confined and bulk solutions of PG and PGME (right).